Heart rate variabilty following 5 weeks of detraining in competitive swimmers - Wood, R. H.; Leleux, S.; Welsch, M. A.; Nelson, A. G.; Kluess, H. A.; Lee, A. M. (Medicina Sportiva, 2001)
The purpose of this investigation was to evaluate HRV following a period of detraining. Therefore, six elite collegiate swimmers were examined for heart period (RR) and HRV (i.e., standard deviation of normal R-R intervals (SDNN), and normalized high- and low-frequency spectral power), and maximal oxygen consumption (VO2max) during incremental arm-ergometry. ECG data were collected for 5 minutes in the supine position under conditions of spontaneous and paced (0.20 Hz) breathing. The athletes were examined 2 weeks prior to the end of the season, at end season, and 1, 2, 3, and 5 weeks post-season. During the first 2 weeks of the post-season period the swimmers reduced their training duration from 20 to 10 hours per week, and during the 3rd through 5th weeks post-season the swimmers did not swim-train. VO2max was significantly reduced by the 2nd week of the post season (34.0 + 8.3 vs. 28.2 + 6.9 ml.kg-1.min-1, respectively) and did not change thereafter. RR intervals were 60-100 msec shorter at the 5th week of detraining than at the other observation periods (regardless of breathing condition), but HRV did not change across the observations. Paced breathing was consistently associated with shorter RR intervals and greater SDNN, but no differences in normalized units of low-and high-frequency power. The results of this investigation are consistent with differential effects of detraining on aerobic power and autonomic modulation of the heart, and provide further indirect evidence for the use of HRV as an index of autonomic modulation of the heart.